PSYCHOLOGICAL DESCRIPTION OF THE CONCEPT OF EDUCATIONAL MOTIVES - Karimjonova Yoqutxon (Journals Park Publishing, 2023)
The social behavior of a person in society, how he behaves, and the position he occupies does not happen by itself without a reason. The concepts of "motive" and "motivation" are used in psychology to explain the implementation of activity and the behavior of a person.